2023
DOI: 10.1039/d3ra02913a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural studies and computational evaluation of cyclophanes incorporating imidazole-2-selones

Abstract: Cyclophanes incorporating o-xylylene or mesitylene-m-cyclophane linked-selone groups are mutually syn in both solid state and solution. While, m-xylylene or p-xylylene cyclophanes linked-selone groups show syn and anti conformations in the solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…[6,[9][10][11][12][13] Recently, there has been an increasing interest in the use of NHC complexes of late transition metals such as Cu, Ag, Au, Pd, or Pt in bioinorganic and medicinal chemistry as antibacterial or anticancer agents. [2,[4][5][6][14][15][16][17][18][19][20][21] In 1993, Arduengo reported the first synthesis of a silver-NHC complex. [22] However, it was not until 1998 that a significant breakthrough was made by Lin et al, [23] who demonstrated that Ag(I)-NHC complexes can serve as highly efficient transfer reagents for the synthesis of other NHC-metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[6,[9][10][11][12][13] Recently, there has been an increasing interest in the use of NHC complexes of late transition metals such as Cu, Ag, Au, Pd, or Pt in bioinorganic and medicinal chemistry as antibacterial or anticancer agents. [2,[4][5][6][14][15][16][17][18][19][20][21] In 1993, Arduengo reported the first synthesis of a silver-NHC complex. [22] However, it was not until 1998 that a significant breakthrough was made by Lin et al, [23] who demonstrated that Ag(I)-NHC complexes can serve as highly efficient transfer reagents for the synthesis of other NHC-metal complexes.…”
Section: Introductionmentioning
confidence: 99%